A cognitive task analysis with implications for designing simulation-based performance assessment. - Mislevy, R. J.; Steinberg, L. S.; Breyer, F. J. (Computers in Human Behavior)
Part of a special issue on computer-based performance assessment of problem solving. An evidence-centered approach to designing a computer-based performance assessment of problem solving is discussed. It is argued that if it is to function effectively as a learning environment, a simulation system must present learners with situations in which they use relevant knowledge, skills, and abilities. Furthermore, if it is to function effectively as an assessment, such a system also be able to evoke and interpret observable evidence about targeted knowledge in a manner that is principled, defensible, and suitable to the purpose at hand. A prototype licensure test, with supplementary feedback, for prospective use in the dental hygiene field is examined. A cognitive task analysis designed to tap the knowledge that hygienists use when assessing patients, planning treatments, and monitoring progress and to elicit the behaviors that manifest this knowledge is outlined. Implications for designing student models, task frameworks, evidentiary structures, and simulation capabilities needed for the proposed assessment are noted.